Health Communication and Decision Making about Vaccine Clinical Trials during a Pandemic - Langford, Aisha T. (Journal of health communication, 2020)
The COVID-19 pandemic has magnified the importance of clinical trials for finding a safe and effective vaccine to protect against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the virus that causes COVID-19. Although communication about vaccines and vaccine hesitancy were challenges long before COVID-19, the twin facts of a pandemic and an "infodemic" of health information, misinformation, and disinformation have raised new challenges for vaccine-related communication and decision-making. The goal of this commentary is to highlight strategies to improve communication and decision-making for adults considering participation in COVID-19 vaccine clinical trials. First, I present a general conceptual model for clinical trial participation that can be applied to various vaccine and other clinical trial contexts. Next, I introduce the ASK (Assume, Seek, Know) approach for enhancing clinical trial participation: (1) assume that all patients will want to know their options, (2) seek the counsel of stakeholders, and (3) know your numbers. The ideas presented in this commentary are intended to enhance vaccine-specific clinical trial communication, decision-making, and literacy, while dually offering strategies and resources that may help reduce vaccine hesitancy and increase vaccine uptake over time.